รัฐธรรมนูญและสถาบันการเมือง : ศึกษารัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2492 - มุกดา เอนกลาภากิจ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
This research is aimed to study constitution of the Kingdom of Thailand 1949 in the context of politics, economy and society by aiming to study the background, intention of the drafters and its enforcement in reality. The study points out that the constitution of the Kingdom of Thailand 1949 which was made by the "Constitution Drafting Assembly" for the first time, it was a constitution with democratic content and royalistic concept. It had formed a bicameral system of government ; the members of parliament were elected by the people and the senators came from appointment by the King. Furthermore, the constitution recognized the freedom of the people widely. But when it was enforced under the government emanating from the coup d Etat 1947, the government was not in favor of this constitution because there were provisions that limited the role of the military politically and affected the political status of the leaders the coup d Etat who were in government too. Nevertheless, military government had to allow this constitution to function due to the lack of popular support as well as acceptance from foreign countries. But the military government itself could not control entirely the army which was very divided into many factions. Moreovers, rivalry and conflict among civilian leaders and military leaders of the People s Party itself led to the instability of the regime. The civilian side could be divided into two groups, a group of Mr. Pridi Phanomyong who gained support from some factions of the navy and Mr. Khuang Aphaiwong, leader of Democrat Party who appointed the senators with the majority in the House of Representatives. In the parliament the senators were very active in controling the government, while outside the parliament there were several revolts this led to the coup d Etat of 1951 which overthrown the constitution. The constitution of 1949 intensely was then replaced by the constitution of the Kingdom of Thailand 1932, which was amended and put into effect so as to perpetuate the military ruling. Moreover, it was found that the royal prerogatives were increased. Enforcement of the constitution of the Kingdom of Thailand 1949 in reality was under the responsibility of the regent as the King was studying overseas. This study also enabled us to know that enforcement of the constitution of the Kingdom of Thailand 1949 was only effective in the parliament. While outside of the parliament it was the repression committed by Thai military leaders to suppress their political enemies. This proved that the administration of Thailand under the constitution of the Kingdom of Thailand 1949 did not carry out the intention of the constitution truly.